Оптимизация разрядноимпульсных технологий на базе применения двухконтурных генераторов импульсных токов - Тертилов, Р.В. (Технічна електродинаміка, 2011)
The approach of double-circuit pulsed current generator synthesis which allows by a given pulse pressure at the working volume by the way of solving inverse problems to carry out the synthesis of circuit parameters and operating modes of double-circuit impulse current generators is developed. The solving algorithm is proposed and the calculation example as well as main results is given.